Rola bezpośrednich inwestycji zagranicznych w rozwoju regionu rolniczo-turystycznego (na przykładzie Warmii i Mazur) - Warżała, Rafał (The Impact of Foreign Direct Investment on the Development of Tourism and Agriculture Region (on Example of Warmia and Mazury), 2005)
This article presents the impact of foreign direct investment on regional development. Warmia and Mazury are regions in Poland with higher than average share of agriculture production and lower than average share of industry production in the structure of GDP. As the main industry enterprises in a region belong to foreign investors, the impact of FDI on structure and production growth is crucial. The results of regression analyses show, that the biggest influence of FDI appears in the case of growth of gross domestic product, gross value added and sold production of industry in a region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 382-386